ANALISIS EKSTERNALITAS USAHA PETERNAKAN AYAM RAS PETELUR DI DESA GADINGREJO UTARA KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Nadya Syafa Azizah; Fembriarti Erry Prasmatiwi; Lina Marlina (Lampung University, 2026)
This study aimed to analyze the income generated from egg-laying hen farming business that included and excluded the externalities and analysed its externalities aspects. The egg-laying hen farming businesses located in Gadingrejo Utara Village, Gadingrejo District, Pringsewu Regency. The respondents in this study included 6 egg-laying chicken farms, and 54 community members lived in the vicinity of the farms and affected by externalities. Data collection was conducted in March 2025. The analytical methods used included quantitative descriptive analysis to analyze the income of the farm , externalities cost, externalities on the community from social, economic, and environmental aspects, and the Contingent Valuation Method (CVM) to calculate WTP and WTA values. The results of the study indicated that the revenue from the egg-laying chicken farming business in Gadingrejo Utara Village that excluded external costs was IDR310,203,850.34 per production cycle. However, after included the the external costs, this revenue decreased to IDR308,723,114.23 per production cycle. Additionally, the Willingness to Pay (WTP) value obtained was IDR2,747,631 per production cycle, while the Willingness to Accept (WTA) value was IDR541,074.07 per production cycle. Positive externalities from the presence of egg-laying chicken farming were included easier access to buy eggs and meat, increased consumption and purchasing power of the community regarding eggs and meat, and the opportunities to build new business. Negative externalities from layer chicken farming were included the uncomfortable feeling of the community related to the waste produced by the farm and the community experiencing headaches and nausea. Key words: externalities, income, laying hens, WTP, WTA